The contribution of human conflict to the development of antimicrobial resistance - Scott J. C. Pallett; Sara E. Boyd; Matthew K. O’Shea; Jessica Martin; David R. Jenkins; Emma J. Hutley (Communications Medicine, 2023)
Human conflict, such as the ongoing conflict in Ukraine, is an important driver of antimicrobial resistance. Here, we describe the challenges when addressing this problem during an ongoing conflict and the opportunities available to reduce the spread of antimicrobial resistance.